Design of a permanent magnet linear motor for oil palm cutter - Abdul Shukor, Fairul Azhar; Wakiwaka, Hiroyuki; Tashiro, Kunihisa; Misron, Norhisam; Nirei , Masami (2014)
The mechanization technique has been proven to increase agricultural productivity. The mechanization technique is applied not only at the end of product processing stage, but it is also involved in the early stage of agricultural activity, such as planting, harvesting, weeding, and etc. In Malaysia, the mechanization technique has been applied to harvest oil palm fresh fruit bunch (FFB) through the development of CantasTM. This tool has tripled the oil palm FFB harvesting productivity. However, due to operational limitation of the CantasTM, a new electrical based tool called E-Cutter has been introduced. In this paper, the design of a permanent magnet linear motor (PMLM) as the E-Cutter’s actuator was looked into. This paper explained the design target, thrust optimization, and the measurement of static thrust characteristics of the manufactured PMLM. The results obtained from the measurement and the simulation output were compared for result validation. As a result, it was found that the characteristics of the measured and simulated static thrust were in agreement.